2013
DOI: 10.1177/1076029613494467
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Procoagulant Cytokine Levels During Pregnancy as Predictors of Adverse Obstetrical Complications

Abstract: Analysis of the maternal plasma for elevated IL-6 and reduced IL-10 levels may be of value in the early prediction of pregnancy complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…However, there was a decline on day 25 of gestation (Figure 1 and Figure 2). It is reported that IL-6 level of maternal plasma is elevated in preterm delivery women during gestation [44], and high serum IL-6 level is associated with pregnancy-induced hypertension in pregnant women [45], which is consistent with our results that there is a decline of IL-6 on day 25 of gestation in ewes.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a decline on day 25 of gestation (Figure 1 and Figure 2). It is reported that IL-6 level of maternal plasma is elevated in preterm delivery women during gestation [44], and high serum IL-6 level is associated with pregnancy-induced hypertension in pregnant women [45], which is consistent with our results that there is a decline of IL-6 on day 25 of gestation in ewes.…”
Section: Discussionsupporting
confidence: 92%
“…Proinflammatory cytokines, such as TNF‐α and IL‐6, and chemokines, such as IL‐8, have been suggested to play key roles in pregnancy outcomes 44 . In particular, IL‐6 and IL‐8 were associated with spontaneous preterm birth 45 .…”
Section: Discussionmentioning
confidence: 99%
“…suggested that IL‐6 might be a crucial factor in the maternal host response as a result of significantly higher levels of IL‐6 in patients with second trimester abortion . As systemic inflammation has been proposed to be responsible for preterm delivery (PTD) and the preterm premature rupture of membranes (PPROM), various cytokines, including IL‐6, have been already studied in different specimens, such as maternal plasma/serum, cervicovaginal and amniotic fluid, and has been found to be both associated and predictive for these adverse pregnancy outcomes . In autoimmune diseases, including Grave's disease, the role of antibodies is known to be T‐cell mediated .…”
Section: Introductionmentioning
confidence: 99%
“…15 As systemic inflammation has been proposed to be responsible for preterm delivery (PTD) and the preterm premature rupture of membranes (PPROM), various cytokines, including IL-6, have been already studied in different specimens, such as maternal plasma/serum, cervicovaginal and amniotic fluid, and has been found to be both associated and predictive for these adverse pregnancy outcomes. [16][17][18][19] In autoimmune diseases, including Grave's disease, the role of antibodies is known to be T-cell mediated. 20 A study by Nielsen et al recently indicated that TPO-Abs enhanced the release of proinflammatory cytokines, such as IL-6, tumor necrosis factor-alpha and interferon-γ, from phagocytic cells in a dose dependent manner, suggesting a possible role of cytokines in the pathogenesis of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%